EFFECTIVENESS OF PRIMARY HEALTH CARE IN THE CONTROL OF PERIODONTITIS: A CRITICAL REVIEW WITH EMPHASIS ON HEALTH PROMOTION STRATEGIES (International Seven Journal of Health Research, 2025)
Periodontitis is one of the most prevalent oral diseases worldwide, with significant impacts on the overall health of patients, especially in vulnerable populations. Primary Health Care (PHC) has proven to be an effective approach to the control and prevention of this condition, through educational strategies, preventive interventions, and early treatments. Several studies show that the integration of oral health into public policies and primary health services contributes significantly to the reduction of periodontitis and other oral disease rates. Educational interventions, such as the promotion of supervised brushing and the application of sealants, have been shown to be effective, especially when health professionals are trained to implement these practices (Martins et al., 2014; Silva et al., 2020). In addition, patient adherence to oral health programs is essential for the success of prevention strategies, being a constant challenge in PHC practices (Freitas & Silva, 2015). This critical review discusses the effectiveness of preventive approaches to periodontitis in Primary Care, focusing on health promotion strategies and the barriers that prevent the implementation of more effective policies.